2013
DOI: 10.1126/science.1232728
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Pollinator Interactions over 120 Years: Loss of Species, Co-Occurrence, and Function

Abstract: Using historic data sets, we quantified the degree to which global change over 120 years disrupted plant-pollinator interactions in a temperate forest understory community in Illinois, USA. We found degradation of interaction network structure and function and extirpation of 50% of bee species. Network changes can be attributed to shifts in forb and bee phenologies resulting in temporal mismatches, nonrandom species extinctions, and loss of spatial co-occurrences between extant species in modified landscapes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
861
2
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 905 publications
(898 citation statements)
references
References 37 publications
23
861
2
12
Order By: Relevance
“…Pollination from both honey bees and native bees is critical for tree fruit and berry crops grown in the Pacific Northwest (Sagili and Caron 2016;Rucker et al 2012). Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Pollination from both honey bees and native bees is critical for tree fruit and berry crops grown in the Pacific Northwest (Sagili and Caron 2016;Rucker et al 2012). Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Other studies using museum collection data have implicated very recent climate change as a possible factor underlying changes in bee abundances (e.g. Cameron et al 2011;Burkle et al 2013), but there are surprisingly few studies that have attempted to infer changes in bee abundance beyond the last 200 years (but see Wilson et al 2014). In the face of likely future climate change, it is important to understand how bees have responded to past climates so that we may better predict future trends.…”
Section: Introductionmentioning
confidence: 99%
“…It then follows that vectoring of parasites by non-host species during shared flower use may be of great importance in pollinator-parasite interactions [15,16]. There is currently great interest in the stress factors affecting pollinators, many of which are showing substantial population declines with knock-on effects on the plants that rely on them for pollination [17][18][19]. Parasites are well established as being an important factor in at least some of these declines, with several bumblebee species showing population declines that correlate with pathogen spillover from commercially produced bumblebees [20][21][22][23][24][25][26][27][28], and honeybee colony losses in many countries being associated with emerging parasites such as the Varroa mite and the microsporidian Nosema ceranae [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%